Overexpression of ca1pase Decreases Rubisco Abundance and Grain Yield in Wheat - Lobo, Ana Karla M. (Plant Physiol, 2019)
Rubisco catalyzes the fixation of CO(2) into organic compounds that are used for plant growth and the production of agricultural products, and specific sugar-phosphate derivatives bind tightly to the active sites of Rubisco, locking the enzyme in a catalytically inactive conformation. 2-carboxy-d-arabinitol-1-phosphate phosphatase (CA1Pase) dephosphorylates such tight-binding inhibitors, contributing to the maintenance of Rubisco activity. Here, we investigated the hypothesis that overexpressing ca1pase would decrease the abundance of Rubisco inhibitors, thereby increasing the activity of Rubisco and enhancing photosynthetic performance and productivity in wheat (Triticum aestivum). Plants of four independent wheat transgenic lines overexpressing ca1pase showed up to 30-fold increases in ca1pase expression compared to the wild type. Plants overexpressing ca1pase had lower numbers of Rubisco tight-binding inhibitors and higher Rubisco activation state than the wild type; however, there were 17% to 60% fewer Rubisco active sites in the four transgenic lines than in the wild type. The lower Rubisco content in plants overexpressing ca1pase resulted in lower initial and total carboxylating activities measured in flag leaves at the end of the vegetative stage and lower aboveground biomass and grain yield measured in fully mature plants. Hence, contrary to what would be expected, ca1pase overexpression decreased Rubisco content and compromised wheat grain yields. These results support a possible role for Rubisco inhibitors in protecting the enzyme and maintaining an adequate number of Rubisco active sites to support carboxylation rates in planta.